CULTIVATION OF POTATO VARIETIES SUITABLE FOR THE SOIL AND CLIMATE CONDITIONS OF THE KHORAZM OASIS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
This article contains information about potato varieties grown in Khorezm region, care, fertilizing methods and irrigation periods.